Elimination of a cholecystokinin receptor agonist 'trigger' in an effort to develop positive allosteric modulators without intrinsic agonist activity. Issue 9 (1st May 2015) - Desai, Aditya J.; Henke, Brad R.; Miller, Laurence J.
Graphical abstract: Abstract: Cholecystokinin (CCK) acts at the type 1 cholecystokinin receptor (CCK1R) to elicit satiety and is a well-established drug target for obesity. To date, small molecule agonists have been developed, but have failed to demonstrate adequate efficacy in clinical trials, and concerns about side effects and potential toxicity have limited further development of full agonists. The use of positive allosteric modulators (PAMs) without intrinsic agonist activity that are active only for a brief period of time after a meal might represent a safer alternative. Here, we propose a possible novel strategy to develop such compounds by modifying the agonist 'trigger' of an existing small molecule agonist. We have studied analogues of the 1, 5-benzodiazepine agonist, GI181771X, in which the N1-isopropyl agonist 'trigger' was modified. While agonist activity was greatly reduced in these compounds, they acted as negative, rather than positive modulators. The parent drug was also found to exhibit no positive modulation of CCK action. Receptor structure–activity relationship studies demonstrated that the mode of docking these derivatives was distinct from that of the parent compound, perhaps explaining their action as negative allosteric modulators. We conclude that this outcome is likely characteristic of the parental agonist, and that this strategy may be more successfully utilized with a parental ago-PAM, possessing intrinsic positive modulatory activity.